The prevalence abnormal urine components as detected by routine dipstick urinalysis: a survey at a primary health care clinic in Mankweng Hospital - Tjale, Malemolla Carl (University of Limpopo (Medunsa Campus), 2009)
Aim: To determine whether routine dipstick urinalysis adds value to the management of patients at Primary Health Care clinic (PHC) in Mankweng Hospital. Objectives: 1. To determine the prevalence of urine abnormality in patients. 2. To determine components of urine (i.e. blood, protein, glucose etc.) that shows abnormality. 3. To determine the association of urine abnormality with regard to age and gender. 4. To estimate the cost of doing dipstick urinalysis. Design: This was a cross-sectional, quantitative survey. A fresh urine sample collected from patients attending the clinic was tested for ten components using UriCHECK 10. The cost of the dipstick test was estimated. Setting: A Primary Health Care clinic in Mankweng Hospital which is a tertiary institution for the province of Limpopo, RSA. Results: A total of 227 patients participated in the study. Of these, 153(67%) were female and 74(33%) were male. Urine abnormality rate was 35%. The most (26%) abnormalities were found in the age group 20-24 years. The prevalence of abnormalities were 19% blood, 12% leukocytes, 4% protein, 11% ketones, 3% glucose, 3% nitrites and 0.4% urobilinogen. The total cost per 100 urine samples was R319.41. Conclusions: The prevalence of initial urinary abnormality at primary care setting is high. There is no significant association between urine abnormality and age. Females are more likely to show urine abnormality. Routine dipstick urinalysis does not lead to significant additional cost and can add value to the management of patients at a Primary Health Care setting.
Thesis (M Med(Family Medicine))--University of Limpopo (Medunsa Campus), 2009.
Keywords: Urinalysis; Urination